2013
DOI: 10.4067/s0716-97602013000200013
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between severity of adult community-acquired pneumonia and impairment of the antioxidant defense system

Abstract: Oxidant/antioxidant imbalance has been reported in some infectious diseases, including community-acquired pneumonia (CAP). The aim was to assess the antioxidant status in adults with CAP and its relationship with clinical severity at admission. Fifty-nine patients with CAP were enrolled and categorized at admission by the FINE score, from July 2010 to October 2012. In the same period 61 controls were enrolled. Plasma samples were obtained at admission for determination of the ferric reducing ability of plasma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 43 publications
0
21
0
1
Order By: Relevance
“…Muravlyova et al18 found that malondialdehyde and reactive carbonyl derivatives were significantly lower in CAP patients than in controls. Castillo et al14 showed that the antioxidant capacity of plasma, as well as glutathione and glutathione disulfide levels, were lower than in controls. In this study, we found that the total and native thiol pools were lower in patients with CAP compared with healthy controls.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Muravlyova et al18 found that malondialdehyde and reactive carbonyl derivatives were significantly lower in CAP patients than in controls. Castillo et al14 showed that the antioxidant capacity of plasma, as well as glutathione and glutathione disulfide levels, were lower than in controls. In this study, we found that the total and native thiol pools were lower in patients with CAP compared with healthy controls.…”
Section: Discussionmentioning
confidence: 98%
“…Many diseases are associated with oxidative stress, including malignancies, cardiovascular disease, and neurodegenerative disease 12. A standard approach for evaluating the response of biological systems to oxidative stress involves measuring the increase or decrease of a redox-sensitive molecule 14. There are few studies in the literature regarding the oxidant/antioxidant ratio in CAP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lower levels of GSH in CAP patients have been observed also in other studies (Kelly, 1999;Rahman and MacNee, 2000;Castillo R. et al, 2013) and suggest that deficit of GSH might predispose to pulmonary inflammation. The protective role of GSH in regard to the lower respiratory tract has been suggested; hence, use of GSH inhalations might be beneficial for cystic fibrosis treatment (Prousky, 2008;Day, 2005).…”
Section: Discussionmentioning
confidence: 52%